Artificial Intelligence in Human Resource Management: Opportunities and Challenges - Saha, Sayan (AG Volumes, 2024)
In order to effectively manage personnel in both domestic and international organisations, businesses are incorporating "artificial intelligence (AI) and other AI-based tools into their human resource management (HRM) practices". Over the past decade, the HRM function has experienced a significant increase in the number of AI-based applications. This has resulted in a new wave of research that is both exciting and innovative. The research investigates the social presence of AI and robotics, the influence of AI adoption on corporate and individual outcomes and the evaluation of HRM practices that are facilitated by AI. In this article review the various literature’s study on opportunities and challenges in human resource management by using artificial intelligence. This review conclude that AI revolutionizes HRM by automating tasks like resume screening, candidate sourcing, scheduling and data entry, allowing HR professionals to focus on strategic roles. Chatbots driven by AI improve employee assistance and tailored learning pathways suggest training according to career objectives and skill sets. To guarantee the ethical application of AI in HRM, organisations must address transparency, bias and regulatory compliance. While aligning AI with company values, HR professionals are instrumental in ensuring impartiality, data privacy and security. AI requires HR teams to develop new skills and organizations must provide proper training. While AI automates tasks, human interaction remains essential for employee relations and conflict resolution.